Advance Health Care Directives and "Public Guardian": The Italian Supreme Court Requests the Status of Current and Not Future Inability. (5th March 2014) - Busardò, Francesco Paolo; Bello, Stefania; Gulino, Matteo; Zaami, Simona; Frati, Paola
Abstract : Advance health care decisions animate an intense debate in several European countries, which started more than 20 years ago in the USA and led to the adoption of different rules, based on the diverse legal, sociocultural and philosophical traditions of each society. In Italy, the controversial issue of advance directives and end of life's rights, in the absence of a clear and comprehensive legislation, has been over time a subject of interest of the Supreme Court. Since 2004 a law introduced the "Public Guardian, " aiming to provide an instrument of assistance to the person lacking in autonomy because of an illness or incapacity. Recently, this critical issue has once again been brought to the interest of the Supreme Court, which passed a judgment trying to clarify the legislative application of the appointment of the Guardian in the field of advance directives.